2021
DOI: 10.1186/s13568-021-01237-1
|View full text |Cite
|
Sign up to set email alerts
|

Seed biostimulant Bacillus sp. MGW9 improves the salt tolerance of maize during seed germination

Abstract: Crop performance is seriously affected by high salt concentrations in soils. To develop improved seed pre-sowing treatment technologies, it is crucial to improve the salt tolerance of seed germination. Here, we isolated and identified the strain Bacillus sp. MGW9 and developed the seed biostimulant MGW9. The effects of seed biopriming with the seed biostimulant MGW9 in maize (Zea mays L.) under saline conditions were studied. The results show that the strain Bacillus sp. MGW9 has characteristics such as salt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…They indicated that the beneficial effects might be due to (i) decreased cell membrane lipid peroxidation, (ii) increased chlorophyll content and antioxidant enzyme activities, and (iii) a better efflux and compartmentation of intracellular ions. Other studies on applying PBs to reduce the deleterious effects of salinity stress have also been reported in several food crops, such as rice [136], maize [134], lettuce [137], cucumber [114], and tomato [90].…”
Section: Salinity Stressmentioning
confidence: 92%
See 1 more Smart Citation
“…They indicated that the beneficial effects might be due to (i) decreased cell membrane lipid peroxidation, (ii) increased chlorophyll content and antioxidant enzyme activities, and (iii) a better efflux and compartmentation of intracellular ions. Other studies on applying PBs to reduce the deleterious effects of salinity stress have also been reported in several food crops, such as rice [136], maize [134], lettuce [137], cucumber [114], and tomato [90].…”
Section: Salinity Stressmentioning
confidence: 92%
“…For example, maize seeds primed with microbial PBs containing Bacillus sp. MGW9 increased the stress tolerance of the maize plants grown in saline-alkali soil [134]. When analyzing two contrasting (salt susceptible and tolerant) rice cultivars under salinity stress conditions, Khan et al [116] found that the natural biostimulant panchagavya significantly enhanced biochemical and physiological characteristics in both cultivars.…”
Section: Salinity Stressmentioning
confidence: 99%
“…Since biostimulants are derived from diversity of sources like plants, humic substances, protein hydrolysate, seaweed extracts, macro-and micro-alga, living microbial cultures and plant growth-promoting microbes (PGPM), etc., these compounds are therefore poorly characterized and their mode of actions are also undefined at cellular and molecular levels. Thus, due to the current knowledge gaps the concepts of PBs are still evolving (Calvo et al, 2014;Li et al, 2021), which is somewhat indicative of the diversity of inputs that can be accepted as PBs.…”
Section: Definitionmentioning
confidence: 99%
“…Growth parameters, such as SRW, SDW, RFW, and RDW, have been used to determine salt stress responses and tolerance in various species, such as cotton [31], maize [32,33], tomato [34], wheat [35], eggplant [36], and rice [9]. RWC and CMS have also been used to assess salt tolerance.…”
Section: Discussionmentioning
confidence: 99%